2000
DOI: 10.1080/030097400447697
|View full text |Cite
|
Sign up to set email alerts
|

Vegan diet alleviates fibromyalgia symptoms

Abstract: The effect of a strict, low-salt, uncooked vegan diet rich in lactobacteria on symptoms in 18 fibromyalgia patients during and after a 3-month intervention period in an open, non-randomized controlled study was evaluated. As control 15 patients continued their omnivorous diet. The groups did not differ significantly from each other in the beginning of the study in any other parameters except in pain and urine sodium. The results revealed significant improvements in Visual analogue scale of pain (VAS) (p=0.005)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(68 citation statements)
references
References 27 publications
0
67
0
1
Order By: Relevance
“…Perhaps the improvements noted in participants were due to weight loss rather than specific composition of the recommended diet. Unfortunately, it is difficult to draw any conclusions, since these few studies had very small sample sizes (ranging from 18–30) and weight or weight loss was not always addressed (Donaldson, Speight & Loomis, 2001; Kaartinen et al, 2000). …”
Section: Discussionmentioning
confidence: 99%
“…Perhaps the improvements noted in participants were due to weight loss rather than specific composition of the recommended diet. Unfortunately, it is difficult to draw any conclusions, since these few studies had very small sample sizes (ranging from 18–30) and weight or weight loss was not always addressed (Donaldson, Speight & Loomis, 2001; Kaartinen et al, 2000). …”
Section: Discussionmentioning
confidence: 99%
“…Key data from the included studies are shown in Table 1. The 12 eligible papers included five randomised controlled trials [52][53][54][55][56], one non-randomised controlled trial [57], three uncontrolled clinical trials [58][59][60], one case-control study [49], and two cross-sectional studies [50,51].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…In total, four different chronic musculoskeletal pain conditions were studied: osteoarthritis (n = 3) [50,52,54], rheumatoid arthritis (n = 4) [51,53,55,59], fibromyalgia (n = 4) [49,[56][57][58], and general musculoskeletal pain (n = 1) [60].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations